The Evaluation of the Digital School Program through the Utilization of GENIUS APP to Enhance Teacher Performance at SDN Tamansari Wonorejo - Jamily, Muhammad Rosyid; Taufiq Harris; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study evaluates the implementation of the Digital School Program through the utilization of the GENIUS APP to enhance teacher performance at SDN Tamansari, Wonorejo District. The evaluation was conducted using the comprehensive CIPP (Context, Input, Process, Product) model. A descriptive qualitative research method was applied, with data collected through in-depth interviews, participatory observation, and documentation studies. The findings reveal that, in terms of context, the program aligns with national digitalization policies and the school’s need for an efficient daily monitoring system. However, in the input aspect, limitations were identified in internet infrastructure and variations in teachers’ digital competencies. The implementation process encountered challenges in the form of resistance to change and suboptimal consistency in application usage. The product or outcomes of the program indicate improvements in administrative efficiency and digital documentation, although its impact on enhancing teachers’ pedagogical performance still requires strengthening. Key supporting factors include the principal’s commitment and training initiatives, while the main inhibiting factors are slow internet connectivity and dual workload demands. The implications of this study provide recommendations for program improvement, such as optimizing infrastructure support, ensuring continuous mentoring, and aligning the application with teachers’ actual workload, to ensure that technology truly serves as an enabler for improving the quality of educational management and teacher performance.